Flouquet, Kassák, Léonard the architecture of images during the interwar period = de architectuur van het beeld tijdens het interbellum - Gonnissen, Adriaan (Mu.ZEE, 2018)
Pierre-Louis Flouquet, Lajos Kassák and Jos Léonard were three visual artists and graphic designers who shaped the interwar years by harnessing the endless possibilities of the line and the plane, and the circle, triangle and square.They shared the conviction that geometric abstraction could be a blueprint for a renewed society after the First World War. It was a message that was advanced through the international avant-garde network of magazines that included, amongst others, Kassák's MA, the Brussels-based 7 Arts with Flouquet as artistic director and Het Overzicht run by Jozef Peeters and Michel Seuphor in Antwerp, with Léonard as an occasional contributor. For Constructivist artists there was no clear distinction between West and East, or centre and periphery. 'Connection' was the keyword, for example between the Belgian and Hungarian avant-garde movements in Antwerp, Brussels, Budapest and Vienna. Exhibition: Kunstmuseum aan Zee MuZEE, Oostende, Belgium (17.06.-04.11.2018)
Issued on the occasion of the exhibition ... held in Mu.ZEE, Ostend, from 16 June 2018 to 4 November 2018
Keywords: Leonard, Jos -- 1892-1957; Flouquet, Pierre-Louis -- 1900-1967; Kassák, Lajos -- 1887-1967; Ausstellungskatalog -- Mu.ZEE -- 16.06.2018-04.11.2018 -- Ostende; Bildband